Knowledge Spillover: The Impact Of Types And Recurrence Of Non-Audit Services On Audit Fees In Malaysia - Merza, Intan Liyana (2012)
The issue of auditor independence has attracted the attention of the government, accounting bodies, and the general public especially after the unfolding of major international and local accounting scandals. The provision of non-audit services by auditors to their clients has been a matter of concern for many years as a threat to the auditor independence. However, the joint provision of non-audit services and audit services is also claimed to create knowledge spillovers that leads to a more efficient audit work. The purpose of this paper was to investigate knowledge spillovers by examining the association between audit fee and non-audit services. A sample of 696 firm-year observations from the financial reports of Malaysian public listed companies over the period 2007-2009 was obtained. The relationship between non-audit services and audit fee was tested by controlling other variables using regression analyses.